정자기장 처리에 따른 실내 관엽식물의 생육 및 생리적 특성 변화 - 이성한(Seong Han Lee); 우수영(Su Young Woo); 곽명자(Myung Ja Kwak) (Weon'ye gwahag gi'sulji, 2012)
The present study aimed to investigate the effect of static magnetic field (SMF) on the growth and physiological characteristics of common indoor plant species. Five foliage plant species, Spathiphyllum spp., Ardisia pusilla DC., Syngonium podophyllum, Peperomia pereskiifolia, and Pilea cadierei were potted into plastic pot equipped with round type anisotropic sintered NdFeB permanent magnet inside the pot. The surface magnetic flux density of each magnet was 3,500 G. After 6 months of growth period, the biomass accumulations of Spathiphyllum, A. pusilla, and P. cadierei under SMF were statistically higher than those of controls. Tissue water content also increased under the influence of SMF in most species. The photosynthetic rate of Spathiphyllum under SMF significantly increased but other species showed no significant difference compared with control. Although there was no significant increase in the photosynthetic rates of A. pusilla, and P. cadierei, they showed remarkable increase in total fresh weight under SMF. This suggests that the demand of assimilates for normal metabolism could be decreased under magnetic influence and thereby biomass accumulation could be more favored. But this is not always true for all plant species because P. pereskiifolia in this experiment, showed no changes in both photosynthetic rate and biomass accumulation. Leaf nitrogen and chlorophyll contents were enhanced significantly in most plant species under influence of SMF. Chlorophyll a/b ratio also increased by SMF. Although there might be a limitation depending on plant species, these results suggest that long-term exposure to SMF might allow plant to have an enhanced acclimation capacity against environmental fluctuations and optimal application of SMF could increase the practical use of indoor plants such as an attempt to improve indoor air quality. 본 연구는 정자기장 처리가 실내 관엽식물의 생육 및 생리적 특성에 미치는 영향과 그 작용 메커니즘을 파악하기 위해 수행되었다. 이를 위해 스파티필름(Spathiphyllum spp), 산호수(Ardisia pusilla DC.), 싱고니움(Syngonium podophyllum), 홀리아페페(Peperomia pereskiifolia) 및 필레아(Pilea cadierei)의 5종 관엽식물을 대상으로 안쪽 바닥면에 표면자속밀도 3,500G의 이방성 NdFeB계 원형 소결영구자석을 장착하여 자성처리한 화분에서 6개월간 생육시켜 나타난 변화를 관찰하였다. 자성처리화분에서의 생육은 스파티필름, 산호수 및 필레아에서 유의성 있는 생육증대를 유도하였으며 대부분의 식물종에서 조직 내 함수율을 증대시키는 것으로 나타났다. 스파티필름은 광합성률 또한 유의성 있게 증대되었으나 산호수 및 필레아의 경우 광합성률의 유의성 있는 증가가 나타나지 않았는데 이는 자성처리화분이 동화산물에 대한 정상적인 대사과정에서의 수요를 감소시킴으로써 생물량 축적에 보다 유리한 조건을 제공하는 것으로 해석된다. 그러나 홀리아페페의 경우 생육이나 광합성에 있어 별다른 차이가 유도되지 않았기 때문에 자성처리화분의 이와 같은 효과는 식물종에 따라 차이를 보일 것으로 생각된다. 실험에 사용된 대부분의 식물종에서 자성처리에 따른 엽 내 질소 및 엽록소 함량과 엽록소 a/b 비율에 유의성 있는 증가가 나타났다. 이와 같은 결과들은 식물종에 따른 제한은 있으나 적절한 자기장 처리를 통해 환경변화에 대한 관엽식물의 잠재적 적응능력을 높이고 실내 환경개선을 위한 실내식물의 활용도를 증대시킬 수 있는 가능성을 제시한다.